IMPLEMENTASI SISTEM INFORMASI PEMERINTAHAN DAERAH REPUBLIK INDONESIA (SIPD RI) PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH ISTIMEWA YOGYAKARTA - Putri, Dea Erninda; Ambarwati, Lilik (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study was to determine the extent of the effectiveness of the implementation of SIPD RI and the obstacles faced during the implementation process. This study uses a descriptive qualitative method with data collection techniques through interviews, documentation studies, and observations. The results of the study indicate that although SIPD RI has great potential in supporting bureaucratic efficiency and data integration, its implementation still requires adjustments in various aspects, such as human resource readiness, system stability, and availability of supporting infrastructure. The conclusion of this study emphasizes the importance of increasing user capacity, periodic system updates, and continuous evaluation so that SIPD RI can function more optimally